Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis